KEHIDUPAN SOSIAL EKONOMI MASYARAKAT TRANSMINGRAN MINANG DI NAGARI KOTO TINGGI KECAMATAN KOTO BESAR KABUPATEN DHARMASRAYA 1980 â 2010 - Marlina, Mira; Yulia, Refni; Aziz, Zulkifli (Pendidikan Sejarah, 2014)
This minithesis Â telling about development of sosia economic people Nagari Koto Tinggi (1980-2010). The formulation of research is: How background arrival and how life sosia economic the people of migrants Minang from year 1980-2010. Purpose of the research is to explanation how development of sosia economic the Minang migrants people in Nagari Koto Tinggi. This research includes the study of sosia economic history following research methods: (1) heuristic, (2) a source of criticism include internal and external criticism, (3) the interpretation of which is the activity, and (4) a the stage of writing a thesis result. The results showed that development of sosia economic the Minang migrants people Nagari Koto Tinggi from year 1980-2010 experience increase where agriculture sector move to plantation sector. The first background the people just rely on allocation from government on the first year, after the assistance end them plant palawija with income Rp. 15.000-200.000 in time one month, now with presence plantation oil palm and rubber income increase on one month accieve RP.3.000.000-5.000.000, development on in the field of sosia economic, the people can build up house, buy car, motorcycle, buy plantation, buy electronics household and the childrens study in the lecture. And so it is in interaction happening among the people of Minang and Java harmonic and peace. Happen the mixing culture (acculturation). Over the result so inferential that Minang trans people Nagari Koto Tinggi experience development sosia culture and in economic of area increase income happen, usually Minang trans people Nagari Koto Tinggi prosperous.